Making the case for a formal Anthropocene Epoch: An analysis of ongoing critiques - Zalasiewicz, J; Waters, CN; Wolfe, AP; Barnosky, AD; Cearreta, A; Edgeworth, M; Ellis, EC; Fairchild, IJ; Gradstein, FM; Grinevald, J; Haff, P; Head, MJ; et al. (Schweizerbart, 2020)
© 2017 The Authors. A range of published arguments against formalizing the Anthropocene as a geological time unit have variously suggested that it is a misleading term of non-stratigraphic origin and usage, is based on insignificant temporal and material stratigraphic content unlike that used to define older geological time units, is focused on observation of human history or speculation about the future rather than geologically significant events, and is driven more by politics than science. In response, we contend that the Anthropocene is a functional term that has firm geological grounding in a well-characterized stratigraphic record. This record, although often lithologically thin, is laterally extensive, rich in detail and already reflects substantial elapsed (and in part irreversible) change to the Earth System that is comparable to or greater in magnitude than that of previous epoch-scale transitions. The Anthropocene differs from previously defined epochs in reflecting contemporary geological change, which in turn also leads to the term's use over a wide range of social and political discourse. Nevertheless, that use remains entirely distinct from its demonstrable stratigraphic underpinning. Here we respond to the arguments opposing the geological validity and utility of the Anthropocene, and submit that a strong case may be made for the Anthropocene to be treated as a formal chronostratigraphic unit and added to the Geological Time Scale.